Electromagnetically induced transparency metamaterial with strong toroidal dipole response - Zhaoyang Shen; Helin Yang; Xiaojun Huang; Tianyu Xiang; Jiong Wu; Yanfei Zhou; Zetai Yu (Materials Research Express, 2020)
This paper designs a planar electromagnetically induced transparency (EIT) metamaterial, which comprises an asymmetric ellipse split resonance ring (AESRR) and cut wire (CW). The proposed EIT metamaterial works in the wide range of incident angles and has polarization-sensitive at two transmission dips. The frequency of transparency peak is 10.67 GHz and maintains a high quality-factor (180.84). By calculating the multipole’s radiated power, it can be found that the toroidal dipole response is enhanced, while the electric dipole response is suppressed at the transparency peak. Interestingly, this paper firstly uses the radiated power of electric dipole to elucidate the polarization sensitivity in two minimal transmissions. Meanwhile, the coupling mechanism of the EIT metamaterial is analyzed by the two-oscillator model and equivalent circuit.